Evaluating Hazard Public Signs at Nusa Penida Tourist Sites for Visitor Safety - Suprastayasa, I Gusti Ngurah Agung; Sunarsa, I Wayan; Darmaputra, Putu Gde Eka; Wiryanata, I Gusti Ngurah Agung; Rusdiarnata, Ketut (Institut Pariwisata Trisakti, 2025)
Public hazard signs are a critical component of tourism safety management. This research therefore aims to investigate the adequacy and effectiveness of public hazard signage at key tourist locations in Nusa Penida Island. Data are collected by questionnaire to tourists, interviews to tourists, local community and government officials and are analyzed qualitatively. The results showed that hazard signs were available in some major tourist spots, yet their number and distribution remained limited and uneven. Many signs were placed in less strategic locations such as parking areas rather than at high-risk zones, reducing their visibility and preventive function. The design and language of the signs were often text-heavy and primarily in Indonesian, with minimal use of international symbols, making them less effective for foreign visitors. Furthermore, most signs only provided general warnings without clear preventive instructions, while their physical condition in many places was poor due to lack of regular maintenance. The implications of these findings suggest the urgent need for improving the quality, placement, and maintenance of hazard signage in Nusa Penida. Collaborative efforts between local government, community, and tourism stakeholders are essential to develop standardized, multilingual, and internationally recognizable signs. Strengthening signage infrastructure will not only enhance visitor safety but also contribute to the sustainable development and positive image of Nusa Penida as a tourism destination. Keywords: hazard, Nusa Penida, public sign, safety and security